The feasibility and acceptability of Project POWER: a mindfulness-infused, cognitive-behavioral group intervention to address mental and sexual health needs of young pregnant women in Liberia - Tamora A. Callands; Kandyce Hylick; Alethea Desrosiers; Shantesica M. Gilliam; Erica N. Taylor; Josalin J. Hunter; Nathan B. Hansen (BMC, 2023)
Abstract Background Following 14 years of civil war in Liberia, war exposure, gender-based violence, and extreme poverty have been identified as key challenges affecting the mental and sexual health of young pregnant women and the health of their unborn children. Despite ongoing efforts to rebuild the country's healthcare infrastructure, empirical and culturally tailored interventions to address the consequences of war are severely limited. To address these concerns, we developed Project POWER (Progressing Our Well-being, Emotions, and Relationships), a mindfulness-infused, cognitive-behavioral intervention for young adult pregnant women. This study sought to 1) assess the feasibility and acceptability of POWER and 2) determine the preliminary efficacy of POWER for improving mental and sexual health outcomes among Liberian war-exposed young adult pregnant women. Methods Eighty-seven women aged 18-25 were recruited from three catchment areas in Monrovia, Liberia to participate in a two-condition, pre-post design quasi-experimental pilot trial. Participants were allocated to the intervention (POWER) or the control condition (a health education program) based on where they resided relative to the catchment areas. Each condition completed a ten-session program delivered over 5-weeks. Feasibility and acceptability of POWER were examined using program logs (e.g., the number of participants screened and enrolled, facilitator satisfaction, etc.) and data from an end-of-program exit interview. The preliminary efficacy of POWER on mental and sexual health outcomes was assessed using repeated measures ANOVA with time and condition as factors. Results Analyses provided preliminary support for the feasibility and acceptability of POWER. Participants attended an average of 8.99 sessions out of 10 and practiced material outside the sessions at least 2.77 times per week. Women in both conditions showed significant reductions in the level of prenatal distress (baseline, M = 16.84, 3-month assessment, M = 12.24), severity of post-traumatic stress disorder (PTSD) symptoms (baseline, M = 11.97, 3-month assessment, M = 9.79),), and the number of transactional sexual behaviors (baseline, M = 1.37, 3-month assessment, M = .94) over time. Participants who received POWER showed significant reductions in the frequency of depressive symptoms (baseline, M = 5.09, 3-month assessment, M = 2.63) over women in the control condition. Conclusions Findings suggest that POWER may be a feasible and acceptable intervention to promote mental and sexual health for young adult pregnant women in Liberia. However, fully powered clinical trials are still needed to determine the efficacy and effectiveness of POWER before recommending its use on a larger scale in Liberia.